2013
DOI: 10.1371/journal.pone.0059629
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Neonatal Blood Dendritic Cells, but Not Monocytes, Are More Responsive to TLRs Stimulation than Their Adult Counterparts

Abstract: The neonatal immune system is often considered as immature or impaired compared to the adult immune system. This higher susceptibility to infections is partly due to the skewing of the neonatal immune response towards a Th2 response. Activation and maturation of dendritic cells (DCs) play an important role in shaping the immune response, therefore, DCs are a target of choice for the development of efficient and protective vaccine formulations able to redirect the neonatal immune response to a protective Th1 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 60 publications
(73 reference statements)
1
12
0
Order By: Relevance
“…Since NK cells produce cytokines like TNF-α, this can explain the higher cytokine production following primo-infection at nine weeks of age. Furthermore, it was demonstrated that neonatal porcine blood DCs were more responsive to stimulation with toll-like receptor ligands than adult porcine blood DCs, since they showed higher expression levels of cytokines and chemokines following stimulation [ 45 ]. After re-infection, higher concentrations of IFN-γ and IL-10 were produced by PBMC, next to higher amounts of the cytokines upregulated after primo-infection.…”
Section: Discussionmentioning
confidence: 99%
“…Since NK cells produce cytokines like TNF-α, this can explain the higher cytokine production following primo-infection at nine weeks of age. Furthermore, it was demonstrated that neonatal porcine blood DCs were more responsive to stimulation with toll-like receptor ligands than adult porcine blood DCs, since they showed higher expression levels of cytokines and chemokines following stimulation [ 45 ]. After re-infection, higher concentrations of IFN-γ and IL-10 were produced by PBMC, next to higher amounts of the cytokines upregulated after primo-infection.…”
Section: Discussionmentioning
confidence: 99%
“…The vacutainers were centrifuged for 30 min at 400 x g and the buffy coat resuspended in 7.5% PBS-EDTA and layered on a 60% FICOLL-PAQUE® Plus gradient (GE Healthcare Bio-Sciences, AB, Uppsala, Sweden) to isolate peripheral blood mononuclear cells (PBMCs). Monocytes were further isolated as described elsewhere [ 37 ]. Briefly, PBMCs were incubated for 20 min with anti-human CD14 microbeads (Miltenyi Biotec Inc., Auburn, CA), and CD14 + monocytes were positively selected using the Magnetic Activated Cell Sorting system (MACS®; Miltenyi) and plated in 24-well plates (Fisher Scientific, Pittsburgh, PA).…”
Section: Methodsmentioning
confidence: 99%
“…Isolated PBMCs were re-suspended in RPMI 1640 medium supplemented with 10% feta bovine serum. PBMCs (1 × 10 6 cells/mL) were stimulated with 5 μg/mL TLR9 ligand CpG ODN for 6, 12, and 24 h according to the reference (Auray et al, 2013). Control cells were cultured under the same condition except no TLR ligand treatment.…”
Section: Methodsmentioning
confidence: 99%